2019
DOI: 10.1002/etc.4414
|View full text |Cite
|
Sign up to set email alerts
|

A Multitracer Approach to Quantifying Resource Utilization Strategies in Lake Trout Populations in Lake Huron

Abstract: Lake ecosystems are threatened by an array of stressors. An understanding of how food webs and bioaccumulation dynamics respond to these challenges requires the quantification of energy flow. We present a combined, multitracer approach using both polychlorinated biphenyls (PCBs) and stable isotopes to trace energy flow, and to quantify how lake trout feeding strategies have adapted to changes in food web structure in 3 basins of Lake Huron (ON, Canada). This combined tracer approach allows the quantification o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 78 publications
(113 reference statements)
1
6
0
Order By: Relevance
“…For example, should prey communities, abundances, and food-web structures be similar across multiple compartments of the same ecosystem, this would be expected to manifest in similar magnitudes and patterns of congener bioaccumulation among individuals of the same species. That basin-specific PCB profiles have now been demonstrated for top predator (Paterson et al 2016) and secondary consumer forage fish species collected from across Lake Huron confirms conclusions regarding the importance of lower trophic level processes in regulating pollutant and energy transfer within the Lake Huron food webs (Bunnell et al 2014;Paterson et al 2014;McLeod et al 2019). Bunnell et al (2014) concluded that bottom-up control mechanisms predominate in terms of nutrient and energy availability and flow in Lake Huron.…”
Section: Discussionmentioning
confidence: 52%
See 4 more Smart Citations
“…For example, should prey communities, abundances, and food-web structures be similar across multiple compartments of the same ecosystem, this would be expected to manifest in similar magnitudes and patterns of congener bioaccumulation among individuals of the same species. That basin-specific PCB profiles have now been demonstrated for top predator (Paterson et al 2016) and secondary consumer forage fish species collected from across Lake Huron confirms conclusions regarding the importance of lower trophic level processes in regulating pollutant and energy transfer within the Lake Huron food webs (Bunnell et al 2014;Paterson et al 2014;McLeod et al 2019). Bunnell et al (2014) concluded that bottom-up control mechanisms predominate in terms of nutrient and energy availability and flow in Lake Huron.…”
Section: Discussionmentioning
confidence: 52%
“…Note differences in axis scales for (C). in gut contents (McLeod et al 2019). In addition, Mida (2010) noted a general absence of mysids in North Channel bloater and rainbow smelt diets.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations